Diterpenoids from the roots of Annona vepretorum Mart. (Annonaceae) - Ana L. M. Souza; Jéssica F. Auzier; Lívia M. Dutra; Victoria L. A. Santos; Emmanoel V. Costa; Jackson R. G. S. Almeida (Química Nova)
Five diterpenoids were isolated from the hexane extract obtained from the roots of Annona vepretorum Mart. (Annonaceae). The chemical structures were determined as ent-3b-acetoxy-kaur-16-ene (1), 17-nor-kaur-16-one (2), ent-kaur-16-en-19-oic acid (3), ent-3b-hydroxy-kaur-16-ene (4) and ent-16b-hydro-kauran-17-oic acid (5). Their structures were identified by spectroscopic analyses (1D and 2D nuclear magnetic resonance (NMR) data) and comparison with literature data. This is the first report on the isolation of compound 2 in the Annonaceae family.